Ocena zasadności łączenia wybranych nieparametrycznych modeli regresji - Trzęsiok, Joanna (On Aggregating Some Nonparametric Regression Models, 2008)
The main goal of the paper is to analyze the feasibility of gaining more accurate predictions by aggregating nonparametric regression models such as MARS, PPR, ACE and AVAS. The aggregating approach is especially effective when single models are weak i.e. the variance of predictions of these models is high. The analysis was performed on benchmark data sets. The results showed that considered models had the built-in variance reduction mechanism, so the increase in the prediction accuracy of aggregating models compared to single models was not significant.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 346-353